2018
DOI: 10.1016/j.ygyno.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in young women with endometrial cancer

Abstract: Young black women are more likely to present with pathologically aggressive, advanced stage tumors. Even after adjusting for these pathologic differences, young black women with endometrial cancer have higher mortality than white women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…These disparities and uneven distribution of major known clinical prognostic factors of survival (e.g. later stage and higher grade of disease) among Blacks are not unique to Florida and have been described in other studies [ 18 20 , 27 , 36 , 37 ]. However, the underlying reasons for these differences remain elusive.…”
Section: Discussionsupporting
confidence: 52%
“…These disparities and uneven distribution of major known clinical prognostic factors of survival (e.g. later stage and higher grade of disease) among Blacks are not unique to Florida and have been described in other studies [ 18 20 , 27 , 36 , 37 ]. However, the underlying reasons for these differences remain elusive.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, a number of studies have shown that both non-White women and underinsured women present with more advanced disease at the time of diagnosis. 26,27 Abbreviations: HR, hazard ratio; ITT, intention to treat.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an analysis restricted to EC patients with advanced stage or recurrent disease, Maxwell et al (9) reported significantly worse survival among black as compared to white women. In a study of EC patients < 50 years of age with stage I or II disease, black women had a 24% higher risk of death than white women (10). Apart from a higher prevalence of aggressive tumor characteristics (11), other factors, including lower socioeconomic status (12), presence of comorbidities (13), and receipt of less complete treatment among black EC patients could contribute to racial disparities in EC survival (14).…”
Section: Introductionmentioning
confidence: 99%